Laparoscopic Urologic Surgery in Malignancies - Rosette, Jean J.M.C.H. de la.; Gill, Inderbir S.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
The horizons of laparoscopic surgery are expanding, such that the overwhelming majority of abdominal urologic procedures have now been performed laparoscopically. In some of these procedures, the laparoscopic alternative has been demonstrated to be superior to its open counterpart; in others comparative analyses are ongoing; and in yet others, only the initial forays into minimally invasive surgery have been undertaken. This book sets out to collate the current body of knowledge on laparoscopic urology under one cover. The authors are respected experts in the field and have provided concise, thoughtful updates on their respective topics. The information contained in this volume will help urologists to increase their laparoscopic knowledge and skills.
Adrenal Cancer -- Transperitoneal Laparoscopic Adrenalectomy in Malignancies -- Retroperitoneal Laparoscopic Adrenalectomy for Malignancy -- Renal Cell Carcinoma I -- Transperitoneal Radical Nephrectomy -- Extraperitoneal Laparoscopic Radical Nephrectomy -- Hand-Assisted Laparoscopic Nephrectomy -- Renal Cell Carcinoma II -- Laparoscopic Partial Nephrectomy -- Cryoablation and Other Invasive and Noninvasive Ablative Renal Procedures -- Bladder Cancer -- Laparoscopic Radical Cystectomy and Intracorporeally Constructed Sigma-Rectum Pouch (Mainz Pouch II) -- Laparoscopic Radical Cystectomy with Orthotopic Bladder Replacement -- Prostate -- Laparoscopic Pelvic Lymph Node Dissection -- Extraperitoneal Laparoscopic Radical Prostatectomy: The Brussels Technique -- Laparoscopic Radical Prostatectomy: The Transperitoneal Antegrade Approach -- The Laparoscopic Radical Prostatovesiculectomy — Transperitoneal Access -- Robotic Radical Prostatectomy: Surgical Technique -- Extraperitoneal Versus Transperitoneal Laparoscopic Radical Prostatectomy -- Handling Complications in Laparoscopic Radical Prostatectomy -- Complicated Cases -- Anticoagulation Therapy During Laparoscopic Surgery -- Laparoscopy in the Obese -- Prior Surgery -- Laparoscopic Radical Nephroureterectomy for Upper Tract Transitional Cell Carcinoma -- Laparoscopic Retroperitoneal Lymph Node Dissection for Testicular Tumors -- Morcellation or Intact Extraction in Laparoscopic Radical Nephrectomy -- Focusing Our Attention on Trocar Seeding! -- Training in Laparoscopy -- Laparoscopic Instrumentation -- Anaesthesia for Laparoscopic Urologic Surgery in Malignancies -- The Future of Laparoscopic Surgery in Urologic Malignancies.
Keywords: Urology; Oncology .; Surgical oncology; Urology; Oncology; Surgical Oncology